2017
DOI: 10.1016/j.tourman.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Tourism-led growth hypothesis in the top ten tourist destinations: New evidence using the quantile-on-quantile approach

Abstract: This paper examines the empirical validity of the tourism-led growth hypothesis in the toptentourist destinations in the world(China, France, Germany, Italy, Mexico, Russia, Spain, Turkey, the United Kingdom, and the United States)using the quantile-on-quantile (QQ) approach and a new index of tourism activity that combines the most commonly used tourism indicators. This methodology, recently introduced by Sim and Zhou (2015), provides an ideal framework with which to capture the overall dependence structure b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
170
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(195 citation statements)
references
References 56 publications
14
170
1
10
Order By: Relevance
“…The findings demonstrate that tourism has a positive impact on growth. Using a quantile-on-quantile model, [22] have investigated the impact of tourism on growth in the top ten tourism destinations over the period 1990 Q1-2015 Q4. The authors have concluded that tourism has a positive and important contribution to economic growth for the country group, including China, France, Germany, Italy, Mexico, Russia, Spain, Turkey, the United Kingdom, and the United States.…”
Section: Tourism and Economic Growth Nexusmentioning
confidence: 99%
“…The findings demonstrate that tourism has a positive impact on growth. Using a quantile-on-quantile model, [22] have investigated the impact of tourism on growth in the top ten tourism destinations over the period 1990 Q1-2015 Q4. The authors have concluded that tourism has a positive and important contribution to economic growth for the country group, including China, France, Germany, Italy, Mexico, Russia, Spain, Turkey, the United Kingdom, and the United States.…”
Section: Tourism and Economic Growth Nexusmentioning
confidence: 99%
“…Another study investigating the tourism-led growth in the top ten tourist destinations reports that tourism has positive relationship with economic growth. The weakest link on those factors are noted for China and Germany, possibly because of the limited importance of the tourism sector relative to other major economic activities in those countries (Shahzad, Shahbaz, Ferrer, & Kumar, 2017). Their studies show that tourism has a little influence on economic growth.…”
Section: Discussion and Business Implicationmentioning
confidence: 99%
“…Tourism development, with its potential to foster economic and social-cultural growth (Jackson & Murphy, 2006;Shahzad et al, 2017), has been proposed as the new way forward for these regional and remote communities. To this end, the Queensland Department of State Development, Infrastructure and Planning in collaboration with the South-West Regional Economic Development Board (SWRED) funded a research project designed to explore ways that these South Western Queensland communities could engage with tourism to increase visitation numbers and drive economic and social gains.…”
Section: Introductionmentioning
confidence: 99%